Acitretin-Induced Necrotizing Sweet's Syndrome in a Patient Having Psoriasis - Karolina Nemeth; Anuradha Bishnoi; David Slater; Graham Colver (Gandhara University, 2023)
A 52-year-old male presented with multiple tender, plum-coloured facial plaques following the treatment with acitretin 50 mg/day for his psoriasis. The lesions subsided over 3 months. Acitretin was restarted at 20 mg/day as psoriasis flared.  A week later, the patient presented with fever and a symmetrically distributed, tender, livid, hemorrhagic papulopustular eruption and large violaceous ulcerated plaques on both soles. Within a week, the patient developed abdominal pain and distension. CT scans of the abdomen showed segments of small bowel wall thickening. Chest X-ray showed consolidation and nodularity of the lung bases. Histopathology demonstrated findings consistent with a diagnosis of Sweet's syndrome. The diagnosis of drug-induced Sweet's Syndrome was established. The patient was treated with a combination of intravenous methylprednisolone and cyclophosphamide. Drug-induced SS has been reported to be associated with many drugs, especially granulocyte-monocyte-colony-stimulating-factor and all-trans-retinoic acid. Although very rare, acitretin-induced SS should be considered in a patient who develops pustulonecrotic skin lesions and systemic upset after intake of acitretin.